Karakteristik Pasien Glioma di RSUD Ulin Banjarmasin Tahun 2018-2020 - Muhammad Rozan Al Ishmat; Agus Suhendar; Fakhrurrazy Fakhrurrazy; Ardik Lahdimawan; Istiana Istiana (Homeostasis, 2022)
Abstract: Glioma is a common primary brain tumor. Characteristics data’s of glioma patients are rarely reported. This study aims to determine the characteristics of glioma patients at Ulin Hospital Banjarmasin in 2018-2020. The method of this research is retrospective descriptive from the patient's medical record. During 3 years there were a total of 77 patients. Most characteristics occurred in the age group > 55 years (20%), male gender (53.3%), address from South Kalimantan (83%), Islamic religion (96.6%), private workers (28.3 %), and BPJS patients (81.7%). All patients had no family history and most had no history of allergies (80%). The most common tumor classification was Grade II (31.6%) and astrocytoma was the histological majority (70%). The most common tumor location was Cerebrum (66.8%) and tumor size was 3-6 cm (33%). the most common clinical symptom was headache (36.6%). The biggest in and out GCS score is GCS 13-15. The length of treatment was 15 days (70%) and the outcome improved (65%). There was a recurrence incidence of 10%. In conclusion, the main characteristics of glioma patients who occurred in the age group > 55 years, male dominant, had no family history and allergies, the main tumor classification WHO Grade II and histological Astrocytoma, located in the cerebrum, 3-6 cm, headache. and decreased level of consciousness were common symptoms, duration of treatment 15 days, improved after treatment, and had a low incidence of recurrence. Keywords: characteristics, gliomas, recurrence, tumor location Abstrak: Glioma merupakan tumor otak primer yang umum ditemukan. Data karakteristik pasien glioma jarang dilaporkan. Penelitian ini bertujuan untuk mengetahui karakteristik pasien glioma di RSUD Ulin Banjarmasin tahun 2018-2020. Metode penelitian ini adalah deskriptif retrospektif dari rekam medis pasien. Selama 3 tahun terdapat total 77 pasien. Karakteristik terbanyak terjadi pada kelompok usia >55 tahun (20%), jenis kelamin laki-laki (53,3%), alamat asal Kalimantan Selatan (83%), agama islam (96,6%), pekerja swasta (28,3%), dan pasien BPJS (81,7%). Semua pasien tidak memiliki riwayat keluarga dan mayoritas tidak memiliki riwayat alergi (80%). Klasifikasi tumor terbanyak adalah Grade II (31,6%) dan Astrocytoma merupakan mayoritas histologis (70%). Lokasi tumor terbanyak adalah Cerebrum (66,8%) dan ukuran tumor 3-6 cm (33%). Gejala klinis terbanyak adalah nyeri kepala (36,6%). Skor GCS masuk dan keluar terbanyak adalah GCS 13-15. Mayoritas Lama perawatan adalah ≤15 hari (70%) dan luaran membaik (65%). Ditemukan kejadian rekurensi sebesar 10%. Kesimpulannya, mayoritas karakteristik dari pasien glioma terjadi pada kelompok usia >55 tahun, laki-laki dominan, tidak memiliki riwayat keluarga dan alergi, klasifikasi tumor mayoritas WHO Grade II dan histologis Astrocytoma, berlokasi di Cerebrum, berdiameter 3-6 cm, nyeri kepala dan penurunan kesadaran merupakan gejala yang sering muncul, lama perawatan ≤15 hari, membaik setelah pengobatan, dan memiliki kejadian rekurensi rendah. Kata-Kata Kunci: glioma, karakteristik pasien, lokasi tumor, rekurensi